Pediatric adrenal incidentaloma - Mihai Cristian Dumitrascu; Alice Elena Ghenea; Mihaela Popescu; Anda Dumitrascu; Mara Carsote; Claudia Mehedintu; Florica Sandru (Amaltea Medical Publishing House, 2021)
The term of "incidentaloma" involves multiple disciplines of the medicine, especially on the era of modern medicine with massive progress of investigations tools that increased the epidemiological implications of this entity. "Endocrine incidentaloma" represents a term mostly used for adrenals and pituitary glands (and less used for thyroid where it is replaced by the term of "thyroid nodule"). Adult adrenal incidentaloma (AAI) is expected to be found up to 5-20% of population depending on age group, co-morbidities, radiological/imaging method (the incidence increases with age), and not in children. We aim to overview the spectrum of pediatric AI (PAI) as an umbrella term for various histological and endocrine conditions. This is a brief narrative review of literature. Inclusion criteria are: PubMed published papers, in extenso articles (English language), the year of publication between 2016 and 2021; the selection is based on clinical relevance. A number of 70 references is included. PAI may be related to various tumors of the cortex and medulla, while AAI mostly means an adrenocortical adenoma with a very good prognostic. AAI diagnostic (based not only on radiological, but also an endocrine assessment) exceptionally underlines an adrenocortical carcinoma or evolves to a malignancy while in pediatric population the eventuality of an incidental adrenocortical carcinoma is not so rare (the non-functional pattern is more frequent in children than in adults). Neural crest-derived tumors may be located at adrenal levels; while ganglioneuroma is a benign tumor which typically respects the incidental detection, neuroblastoma is mostly aggressive and the clinical presentation suggestive for a malignancy is more frequent rather than a completely asymptomatic picture. 10-14% of pheochromocytomas are incidentally detected; however, the adrenalectomy is imperative, regardless the phenotype. PAI represents a large multidisciplinary field which is still a matter of debate in certain areas. The key message is the fact that accidental detection of an adrenal mass on an apparently healthy child needs careful examination; serial follow-up is less likely the elective approach (opposite to adult population) since adrenalectomy provides adequate histological report in order to sustain the endocrine and imaging workup.